2007
DOI: 10.1080/17480270801945439
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a two-stage heat treatment process on the mechanical properties of full construction timber

Abstract: This study investigated the impact of an industrially used two-stage heat-treatment method on the mechanical properties of full construction timber. Bending tests of full-size Norway spruce posts demonstrated changes due to heat treatment, such as a decrease in the density and bending strength, as well as an increase in the modulus of elasticity (MOE). The variability in bending strength and MOE appeared to be higher for treated posts and as a result the 5% values decreased, especially for the bending strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 7 publications
4
13
1
2
Order By: Relevance
“…Brischke et al, 2006Schuh, 2008), whereas the MOR of the weathered specimens decreased significantly. This impact of weathering stresses on static strength properties was also reported by Boonstra et al (2007) and Welzbacher et al (2011). Consequently, the decrease in RIM represents the decrease in structural integrity of the cell wall on a microlevel, whereas the decrease in MOR represents the combination of microstructural changes and (macro)impacts of cracks and other defects.…”
Section: Resistance To Impact Millingsupporting
confidence: 74%
“…Brischke et al, 2006Schuh, 2008), whereas the MOR of the weathered specimens decreased significantly. This impact of weathering stresses on static strength properties was also reported by Boonstra et al (2007) and Welzbacher et al (2011). Consequently, the decrease in RIM represents the decrease in structural integrity of the cell wall on a microlevel, whereas the decrease in MOR represents the combination of microstructural changes and (macro)impacts of cracks and other defects.…”
Section: Resistance To Impact Millingsupporting
confidence: 74%
“…In the MOR values, all values except HTD33 increased by varying rates (26,72-55,29%) in HTD samples compared to the control sample. In contrast to these results, Boonstra et al (2007b) obtained a 6% reduction in bending strength, but a 17% increase on MOE in treated Norway spruce wood.…”
Section: Data Incontrasting
confidence: 84%
“…In addition, Esteves et al (2007a) found 40% and 50% decreases in bending strength for pine and eucalypt wood, respectively, while the MOE was little affected. Reduced strength properties have also been reported by Kubojima et al (2000), Poncsák et al (2006), Sundqvist et al (2006), Boonstra et al (2007a), Esteves et al (2007b), Shi et al (2007) and Korkut et al (2008).…”
Section: Introductionmentioning
confidence: 59%